Co mówi, kiedy nikt nie mówi. Praktyka poetycka Alice Oswald jako przekład - Heydel, Magda (Poznańskie Studia Polonistyczne. Seria Literacka, 2018)
The paper looks at two book-length poems by Alice Oswald’s: Dart (2002) and Memorial (2011) as translation projects, with an aim to understand both the nature of Oswald’s poetic practice and her concept of what is the meaning and goal of translation in creative work. I claim that translation, in the special sense the poet gives to this term, is at the very core of her work. In my analysis I concentrate on the physical aspect of Oswald’s poetic practice, the role of the body, movement in space, muscular effort, rhythm and memorization of poetry in her projects. I also look at the ways of crossing the divide between the human and non-human, linking language to the voice of the natural world and returning to oral poetry in her work.